Calculation of Preferable Profitableness of Share at Attraction of Means Within the Framework of Share Funds of the Real Estate - РаспутинАлексей Владимирович (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2011)
One of sources of financing of building projects can be the closed share investment funds. From a position of investors such source is risky as to define resultant profitableness before project end difficult enough. For attraction of investors it is offered to establish the fixed rate of profitableness under shares, the algorithm of calculation of such rate is considered in article.